Giardia lamblia assemblages and their correlation with the severity of diarrhoea: A review article - Raja, Nadeem Sajjad; Naeem, Mohammad Abdul; Cheema, Kanwal Hassan; Sarwar, Afia (Infectious Diseases Journal of Pakistan, 2024)
Background: Giardia lamblia is responsible for a range of clinical conditions, from asymptomatic to acute or chronic symptomatic forms. The genetic variability of Giardia lamblia raises the possibility of a relationship between its assemblages and the clinical severity of giardiasis. We conducted a review of the literature from 2001 to 2023 to explore the association between G. lamblia assemblages and the severity of diarrhea. Material and Methods: A search was performed through databases of PubMed, WHO, Health Protection Agency, the UK and Centre of Disease Control USA websites and Medline. This search yielded 47 studies from 2001 to 2023 as only those articles providing information on the correlation between different assemblages of G. lamblia and the severity of the disease were included. Results: Out of a total of 47 studies that were included, only 26 studies showed a meaningful comparison. 12 studies showed no difference between different G. lamblia assemblages and the severity of giardiasis, while 14 studies demonstrated the link between G. lamblia assemblage and the severity of the disease. Conclusion: Numerous studies have attempted to identify the link between its assemblage profile and the symptoms it causes but with little success. However, the findings of these studies are contradictory and inconclusive, making it difficult to establish a clear association. However, the divergence in findings suggests that a definitive correlation cannot yet be established. To fully understand the link between assemblages and severe diarrhea, further molecular studies are needed, especially in large populations residing in endemic regions. Keywords: Giardia lamblia, Diarrhea, Assemblages